Pengaruh Kompensasi Langsung Dan Tidak Langsung Terhadap Produktivitas Kerja Karyawan Hotel Bintang Lima Di Kawasan Badung Bali - Ni Wayan Mega Sari Apri Yani; Ayu Suwita Yanti; I Made Darsana (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
The aim of this research is to determine and analyze the effect of direct compensation and indirect compensation on the work productivity of employees at the Five Star Hotel Badung Bali. This research is quantitative research with a type of causal research. Data collection was carried out by distributing questionnaires to 70 employees of the Five Star Hotel Badung Bali. The sampling technique uses simple random sampling. The data analysis technique uses descriptive analysis to determine the profile of respondents and multiple linear regression analysis to test the research hypothesis. The results of this research conclude that direct compensation and indirect compensation have a significant effect on the work productivity of employees at the Five Star Hotel Badung Bali.